Effects of Ethical Leadership on Trust, Affective Commitment, and Organizational Deviance at the Hotel Industry in Cameroon - Mbi, Tarkang Mary Magdaline Enow (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Purpose – The thesis investigates the effects of ethical leadership on trust in leaders’ affective commitment and employee organizational deviance, the impact of trust on affective commitment and organizational deviance and the effect of affective commitment on organizational deviance. Methodology – Data used were obtained from 150 frontline employees working in four-star hotels in Cameroon. A convenience sampling and cross-sectional research method were implemented for that data collection. Correlation, regression, and path analysis were used for data analysis Results–The present research endorses that ethical leadership positively affects trust in leaders and affective commitment and negatively influences organization deviance. Furthermore, it is confirmed by the present study that, trust positively affects affective commitment and negatively affects organizational deviance. Last but not the least, affective commitment negatively influences organizational deviance. Hence, the perception of ethics in leadership by employees on their leaders will instigate their trust in them. They will become committed to their jobs and avoid any deviant behaviour or actions that will negatively affect the growth of the hotel. Managerial implications – The results of the present study should help to encourage authorities in the hospitality industry to improve in hotel prospectus by enhancing ethical leadership performances for forthcoming leaders in the industry. Managers’ and leader’s ethical behavior and their senses of responsibility have a great impact on employees’ attitudes and practices. Leaders should invest in measures that will nurture trust and promote effective intellectual contacts in the workplace, thereby discouraging deviant employee actions. Original Contribution – This study underwrites to the build of literature on the academic enlightenment of the significances of ethical leadership on trust in leaders in the hotel industry, as well as to the growing body of studies based on affective organizational commitment and organizational deviance in hotel industry. Keywords: Ethical Leadership; Trust in Leaders; Employee Affective Commitment; Organizational Deviance; Cameroon.

ÖZ: Amaç – Bu tez, etik liderliğin liderlerin duygusal bağlılığına güven ve örgütsel sapma üzerindeki etkilerini, güvenin duygusal bağlılık ve örgütsel sapma üzerindeki etkilerini ve duygusal bağlılığın örgütsel sapma üzerindeki etkisini incelemektedir. Yöntem – Kullanılan veriler Kamerun'daki dört yıldızlı otellerde çalışan 150 ön hat çalışanlarından elde edilmiştir. Veri toplamada kolayda örnekleme ve kesitsel araştırma yöntemi uygulanmıştır. Veri analizi için korelasyon, regresyon ve yol analizi kullanılmıştır. Sonuçlar – Mevcut araştırma etik liderliğin liderlere duyulan güveni ve duygusal bağlılığı olumlu yönde, örgütsel sapmayı olumsuz yönde etkilediğini ortaya koymuştur. Ayrıca, güvenin duygusal bağlılığı olumlu yönde etkilediği ve örgütsel sapmayı olumsuz yönde etkilediği bu çalışma ile doğrulanmıştır. Duygusal bağlılığın örgütsel sapmayı olumsuz yönde etkilediği de görülmüştür. Dolayısıyla, çalışanların liderleri üzerindeki liderlik etiği algısı onlara olan güvenini artıracaktır. İşlerine bağlı kalacaklar ve otelin büyümesini olumsuz yönde etkileyecek sapkın davranışlardan kaçınacaklardır. Yönetsel Çıkarımlar – Bu çalışmanın sonuçları, otelcilik sektöründeki yetkilileri, endüstrideki yeni liderlerin etik liderlik performanslarını artırmaya odaklanarak otellerini iyileştirmeye teşvik etmelidir. Yöneticilerin ve liderlerin etik davranışlarının ve sorumluluk duyularının çalışanların tutum ve eylemleri üzerinde büyük bir etkisi vardır. Liderler, işyerinde güveni besleyecek, etkili entelektüel temasları teşvik edecek ve böylece sapkın çalışan davranışını engelleyecek önlemlere yatırım yapmalıdır. Özgün Katkı - Bu çalışma, otel endüstrisindeki liderlere olan güven konusunda etik liderliğin öneminin anlaşılmasının yanı sıra, otel endüstrisinde duygusal örgütsel bağlılık ve örgütsel sapmalara dayanan sonuçların akademik açıdan aydınlatılmasına ilişkin literatürün oluşturulmasına katkıda bulunmaktadır. Anahtar Kelimeler: Etik Liderlik; Liderlere Güven; Duygusal Bağlılık; Örgütsel Sapma; Kamerun.
Doctor of Philosophy in Tourism Management. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Tourism, 2019. Supervisor: Assoc. Prof. Dr. Ali Öztüren.
Keywords: Tourism; Organizational behavior--Psychology, Industrial--Organizational effectiveness--Hotel Industry--Cameroon; Work Attitudes--Job Satisfaction itizenship--Organizational Climate; Human Resources Management--Leadership; Ethical Leadership; Trust in Leaders; Employee Affective Commitment; Organizational Deviance; Cameroon